BGer 1C 242/2010 vom 19. Juli 2010 - Bundesgericht (2010)
Petitionsrecht bzw. politische Rechte [1C_242/2010] Petitionsrecht bzw. politische Rechte [1C_244/2010] Petitionsrecht bzw. politische Rechte [1C_246/2010] | Grundrecht